(untitled) (Texas Journal of Multidisciplinary Studies, 2026)
This article presents a methodology for developing students’ information modeling skills in the process of teaching the “Optics” section of physics within higher education. The relevance of the study is determined by the need, in the context of the digital transformation of education, for students not only to acquire theoretical knowledge but also to develop competencies in visualizing and analyzing complex physical processes using digital models. The paper analyzes common misconceptions encountered by students when mastering concepts related to optics and outlines effective approaches for overcoming these difficulties through the use of information technologies. Furthermore, based on the CIEE model within the integrated informationeducational environment of higher education institutions, methods are proposed for systematically organizing the learning process around information objects and processes. The findings of the study indicate that the information modeling approach contributes to the enhancement of students’ critical thinking skills and promotes a deeper understanding of physical phenomena. The proposed methodological recommendations are intended for students majoring in physics as well as for higher education instructors and have practical significance in the design of educational materials within a digital environment